2010
DOI: 10.1158/1940-6207.capr-09-0096
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Phase 3 Skin Cancer Prevention Study of α-Difluoromethylornithine in Subjects with Previous History of Skin Cancer

Abstract: Preclinical studies have shown that the inhibition of ornithine decarboxylase (ODC) by α-difluoromethylornithine (DFMO) and resultant decreases in tissue concentrations of polyamines (putrescine and spermidine) prevents neoplastic developments in many tissue types. Clinical studies of oral DFMO at 500 mg/m 2 /day revealed it to be safe and tolerable and resulted in significant inhibition of phorbol ester-induced skin ODC activity. Two hundred and ninety-one participants (mean age, 61 years; 60% male) with a hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 26 publications
2
79
0
1
Order By: Relevance
“…Thus, the link between ODC and NMSC is indisputable, validating ODC as both a chemoprevention and chemotherapeutic target. In fact, a recent phase III chemoprevention trial demonstrated that ␣-difluoromethylornithine, a suicide inactivator of ODC, markedly reduces the incidence of new basal cell carcinoma in subjects with a history of skin cancer (18). Earlier studies showed that topical ␣-difluoromethylornithine administration reduced the incidence of actinic keratosis, a precursor of squamous cell carcinoma, in subjects at high risk for NMSC (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the link between ODC and NMSC is indisputable, validating ODC as both a chemoprevention and chemotherapeutic target. In fact, a recent phase III chemoprevention trial demonstrated that ␣-difluoromethylornithine, a suicide inactivator of ODC, markedly reduces the incidence of new basal cell carcinoma in subjects with a history of skin cancer (18). Earlier studies showed that topical ␣-difluoromethylornithine administration reduced the incidence of actinic keratosis, a precursor of squamous cell carcinoma, in subjects at high risk for NMSC (56).…”
Section: Discussionmentioning
confidence: 99%
“…A link between neoplastic transformation and increased ODC enzyme activity, as well as increases in intracellular putrescine and spermidine, have been well documented in animal models of skin carcinogenesis and other epithelial tumors (11)(12)(13)(14)(15)(16)(17). Moreover, a link between human nonmelanoma skin cancer (NMSC), the most prevalent cancer in the United States, and elevated ODC enzyme activity levels has been described (18). The induction of ODC activity during tumor development has been attributed to both increased Odc gene transcription and translation of the ODC mRNA (9,19).…”
mentioning
confidence: 99%
“…130 There is also some evidence that a-difluoromethylornithine, an irreversible inhibitor of the pathway that produces polyamines in humans, may reduce the risk for BCC in those with a history of keratinocyte cancer, although treatment-associated audiometric abnormalities have been reported. 131,132 Although there is evidence that oral celecoxib makes NMSC in general, and BCC in particular, less likely in patients with previous NMSC, the potential benefits should be weighed against the significant risk for a cardiovascular event that is associated with this medication. 133,134 The dietary supplements b-carotene and selenium have also been studied, and are not recommended for reducing risk for BCC or cSCC in patients with a history of BCC.…”
Section: Follow-up and Reducing Risk For Future Skin Cancersmentioning
confidence: 99%
“…[116][117][118][119]123,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141] …”
Section: Follow-up and Reducing Risk For Future Skin Cancersunclassified
“…A recent study showed that DFMO, when combined with sulindac (an NSAID), significantly reduced the risk of recurring colorectal polyps (Meyskens et al, 2008). Another controlled phase III clinical trial showed that DFMO might reduce the recurrence of basal cell carcinoma (Balley et al, 2010). In addition, DFMO is currently being researched in prevention of esophageal cancer (Sinicrope et al, 2011) and breast cancer (Izbicka et al, 2010).…”
Section: Difluoromethylornithine (Dfmo)mentioning
confidence: 99%